Marking the Field of Industrial Relations in Poland: Theoretical Inspirations and Research Traditions - Czarzasty, Jan (Warsaw Forum of Economic Sociology, 2020)
The article aims at describing the theoretical inspirations and research traditions behind the evolution of industrial relations in Poland. The account of global theoretical debate since the emerging of the field in the first half of the 20th century is delivered, followed by the overview of academic debates and research concerning the field since the times of state socialism (1945–1989) until the present day in Poland. In the conclusion, it is stated that in theoretical terms the field of industrial relations has remained underdeveloped.